GaN nanowires on diamond. (15th June 2016) - Hetzl, Martin; Schuster, Fabian; Winnerl, Andrea; Weiszer, Saskia; Stutzmann, Martin
Abstract: The current research of GaN nanowires on diamond substrates is reviewed and extended by recent results. Both the self-assembled and the selective area growth mechanisms using plasma-assisted molecular beam epitaxy are summarized. Structural and optical properties of as-grown nanowires as well as doping-related issues are discussed and compared to nanowires on silicon substrate. The electronic characteristics of p-diamond/n-GaN nanowire heterojunctions are addressed theoretically by band structure simulations and experimentally by transport measurements. Finally, electroluminescence of a fabricated prototype nanoLED device is demonstrated.